Incidental Chylous Ascites at the Time of Cesarean Section - Kida A. Thompson; Antoun Al Khabbaz (Case Reports in Obstetrics and Gynecology)
Chylous ascites has multiple etiologies including malignancies, liver cirrhosis, intraperitoneal infections, and trauma. It is rarely reported in pregnancy. We report a case of chylous ascites noted at the time of cesarean section performed at 35 weeks of gestation on a patient with preeclampsia and suspected placental abruption. The diagnosis and treatment of chylous ascites as well as the pregnancy outcome are presented. A literature review of chylous ascites in pregnancy is discussed as well.